Comparison of long COVID, recovered COVID, and non-COVID Post-Acute Infection Syndromes over three years - Caleb R. Carr; Nicole L. Gentile; Jeanne Bertolli; Warren Szewczyk; Jin-Mann S. Lin; Elizabeth R. Unger; Quan M. Vu; Nona Sotoodehnia; Annette L. Fitzpatrick (PLoS ONE, 2025)
Background Comparing the characteristics of patients with long COVID to those with other post-acute infection syndromes (PAIS) could potentially provide clues to common underlying disease processes that may affect patient recovery. Methods We identified records of patients who had documented SARS-CoV-2 tests in the University of Washington Medicine electronic health record (EHR) database from January 1, 2019, through January 31, 2022 (n = 139,472). Patients were classified into three groups: 1) long COVID defined by a positive SARS-CoV-2 test and a long COVID-related diagnosis code (n = 580); 2) recovered COVID defined by a positive test and no long COVID associated diagnosis codes (n = 7,437); and 3) non-COVID PAIS defined by a negative test, non-SARS-CoV-2 related PAIS diagnosis codes, and no COVID related codes (n = 106). Using multivariate logistic regression, we compared the clinical characteristics of these groups at three timeframes to address preclinical, acute and post-acute diagnoses: before index SARS-CoV-2 test, within 30 days of index test, and > 30 days after index test. Results The long COVID group had a higher Charlson comorbidity index [median (IQR), 2 (0–4)] than the other two patient groups [median (IQR), 1 (0–3) and 1 (0–3)]. The long COVID and non-COVID PAIS patients were older and had greater smoking exposure than the recovered COVID group. Compared to the recovered COVID control group, the long COVID group had more health problems prior to the infection, including respiratory and metabolic as well as more severe infections and comorbidities based on the ICD codes found in the acute phase records. In the post-acute timeframe, many symptoms were more likely to be associated with long COVID than recovered patients with COVID-19 including abnormalities of heart beat [OR (95% CI), 5.31 (3.96–7.13)], cognition, perception, or emotional state symptoms [OR (95% CI), 5.14 (3.81–6.92)], malaise and fatigue [OR (95% CI), 4.20 (3.13–5.63)], and sleep disorders [OR (95% CI), 2.47, (1.79–3.43)], all p < 0.05. In contrast, the non-COVID PAIS group shared many similarities with the long COVID group across all three timeframes. Conclusions Patients diagnosed with long COVID were more similar to patients with a non-COVID-related PAIS than to recovered patients with COVID-19. This suggests risk factors for PAIS may be similar and independent of the infectious agent.